Is pregnancy in MS patients safe and what is its impact on MS course? Real World evidence of 1533 pregnancies in Czech Republic - Hradilek, Pavel; Meluzinova, Eva; Zapletalova, Olga; Hanulikova, Petra; Horakova, Dana; Woznicova, Ivana; Pavliska, Lubomir; Stetkarova, Ivana; Valis, Martin; Stourac, Pavel; Adamkova, Jana; Ampapa, Radek; et al. (Multiple sclerosis and related disorders, 2022)
BACKGROUND: A special care of MS women planning a pregnancy is highly demanding especially in the terms of disease modifying treatment (DMD) decisions and counselling regarding periods of conception, pregnancy and postpartum period. OBJECTIVE: To provide data about impact of pregnancy, delivery or miscarriage/artificial abortion on MS disease course in Czech women with MS based on analysis of retrospective data from the Czech national registry ReMuS. METHODS: The analysis focused on women with MS with at least one record of pregnancy in the registry. Clinical data (EDSS, relapses) were collected prior to conception, during pregnancy and after delivery or miscarriage/artificial abortion. These data were analysed according to baseline characteristics of DMD treatment prior to conception and according to breastfeeding status. RESULTS: A total of 1 533 pregnancies were analysed from the period of 2013 until 31st December 2019. The occurrence of relapses and worse EDSS was significantly related to the treatment with escalation therapy prior to conception. Relapses were significantly more frequent in women who breastfed less than 3 months than in women who breastfed more than 3 months or did not breastfeed at all. Patients treated with either fingolimod or natalizumab prior to pregnancy were significantly more likely to develop relapses during pregnancy. CONCLUSION: Pregnancy and postpartum period were generally safe for Czech women with MS. Better disease outcomes were observed in those who had been treated with first line injectable DMDs prior to conception and those who either breastfed more than 3 months or did not breastfeed at all. We confirmed the assumption of rebound phenomenon of MS after discontinuation of treatment due to planned pregnancy both for fingolimod and natalizumab.
Keywords: Multiple sclerosis; Czech national registry ReMuS; retrospektivní studie; Multiple Sclerosis; Česká republika; Relapses; fingolimod hydrochlorid; Pregnancy; těhotenství; Natalizumab; Czech Republic; Fingolimod Hydrochloride; lidé; ženské pohlaví; Humans; EDSS; natalizumab; Retrospective Studies; Female; roztroušená skleróza